Access and Use of Specific Dental Services in HIV Disease - Ana Karina Mascarenhas, BDS, DrPH; Scott R. Smith, RPh, MSPH, PhD (Blackwell Synergy, 2000)
This study examined factors associated with the use of specific dental services by persons with HIV disease. Methods: The data were derived from 1,588 adults who participated in a series of up to six interviews as part of the AIDS Cost and Service Utilization Surveys. Use of dental services such as examinations, x-rays, cleaning, fillings, extractions, root canals, crown and bridge or dentures, and periodontal procedures were evaluated using logistic regression and generalized estimating equations were applied